Methodology in language research: a sailing between Scylla and Charybdis - Duncker, Dorthe (2022)
Unlike most linguistic theories, integrational linguistics does not include a methodology for linguistic inquiry. Integrationists are critical of the methodologies and assumptions of modern linguistics and find the notion of linguistic data highly problematic. For this, integrationists have taken a lot of heat from researchers from data-driven research traditions who ask for a methodological alternative and find the lack of empirical integrational research frustrating. In this essay, I consider some of the background for the integrational critique of linguistic methodologies and discuss how to address the difficulties pertaining to linguistic data. I conclude with an empirical example to illustrate the problems as well as their possible solution.